Ecology of Indian Desert VIII, on the Water Relations and Assimilate Balance of some Desert Plants - Mathur, Tara; Sen, D N (Annals of Arid Zone, 2016)
A study an the water relations and the assimilate balance of four desert plant species has been made after the rains were over and the dry period started in Western Rajasthan for a period of four-six months. It was observed that a reduction in the water loss and stomata1 openings took place when the soil water decreased. The percentage of absolute moisture in Colotropis procera was found to be the maximum among the four species, probably because of latex. It was minimum in Prosopis Cineraria. The percentage of relative water content of Prosopis Cineraria, Prosopis juliflora and Tephrosia purpurea decreased but in Calotropis procera increased with decrease in soil moisture. The polyccharides were detected only in November and the presence of monosaccharides in summer month had led to a high osmatic potential, resulting in an enhanced water uptake. The values of total nitrogen do not appear to show any particular trend in relation to the survival or otherwise of these desert plant species.